2005
DOI: 10.1002/eji.200425850
|View full text |Cite
|
Sign up to set email alerts
|

The advantage of mucosal immunization for polysaccharide‐specific memory responses in early life

Abstract: The aim of vaccination is to rapidly elicit protective immunity and generate memory for sustained protection. We studied the induction and persistence of polysaccharide (PS)-specific memory in neonatal and infant mice primed with pneumococcal conjugate (Pnc1-TT) by assessing the response to native pneumococcal PS (PPS-1), the kinetics of the PPS-1-specific IgG response to a second Pnc1-TT dose and affinity maturation. A subcutaneous (s.c.) Pnc1-TT booster induced a rapid increase in PPS-1-specific IgG, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 34 publications
5
38
0
Order By: Relevance
“…Our previous studies have shown that immunization of mice with conjugate vaccines can induce PS Abs and protective immunity in early infancy, but both immunogenicity and protective efficacy is significantly lower than in adults [34,42]. This murine infant immunization model against S. pneumoniae clearly reproduces the main features of human infant immune responses to native capsular PPS and pneumococcal conjugate vaccines, as shown for serotypes 1, 6B and 19F, as well as the relative protective efficacy of such vaccines.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Our previous studies have shown that immunization of mice with conjugate vaccines can induce PS Abs and protective immunity in early infancy, but both immunogenicity and protective efficacy is significantly lower than in adults [34,42]. This murine infant immunization model against S. pneumoniae clearly reproduces the main features of human infant immune responses to native capsular PPS and pneumococcal conjugate vaccines, as shown for serotypes 1, 6B and 19F, as well as the relative protective efficacy of such vaccines.…”
Section: Discussionsupporting
confidence: 56%
“…Unresponsiveness of lymphoid-mediated signals at the level of neonatal follicular dendritic cell precursors has recently been shown to be a major limiting factor, leading to limitations in germinal center induction, Ab-secreting cells and Ab response [43]. Age-dependent limiting factors for Ab responses to conjugate vaccines have not yet been fully identified, but we have recently shown that the immunization route affects the recall response to PPS in mice primed with a conjugate as neonates [42]. Here, we show that a weak carrier-specific T cell response obtained after immunization with a monovalent pneumococcal conjugate vaccine in early life is responsible for the low levels of IgG Abs to the PPS.…”
Section: Discussionmentioning
confidence: 97%
“…Avidity of IgG Abs was measured by ELISA with a kaliumthiocyanate (KSCN) elution step (19). Cell wall PS-neutralized standard and sera (1:50)…”
Section: Ab Aviditymentioning
confidence: 99%
“…Using an early-life murine model of pneumococcal vaccination and challenge that reproduces the main features of human infant response to pneumococcal conjugate vaccines (16), we have reported that coadministration of the nontoxic adjuvant LT-K63 (nontoxic mutant of Escherichia coli heat-labile enterotoxin) (17,18) with pneumococcal polysaccharide of serotype 1 conjugated to tetanus toxoid (Pnc1-TT) enhances protection against pneumococcal infection, correlating with enhanced PPS-specific Ab levels (16), avidity (19), and activation of B cells, T cells (20), and dendritic cells in spleen (21).…”
mentioning
confidence: 99%
“…Other reasons for using mucosal routes of immunization include the practicability of administering the vaccine without injections, and therefore the reduction of injection site reactions, and the possibility of vaccination at a very early age of life in the presence of passively acquired maternal antibodies (Tab. I) [15].…”
Section: Rationale For Mucosal Vaccinationmentioning
confidence: 99%